Miracle 14: Transparency in Indonesia’s State-Owned Enterprises - Yasin, Muhammad; Nursadi, Harsanto (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2021)
In administrative science and administrative law, public information disclosure has universally recognized as important partway to good governance. There is an explosive recognition of the world to freedom of information act. Freedom of information or right to information is a inseparable part of transparency principle in governance. Enacting freedom of information act is an effort not only to make government better, but also to create trust among government, the business, and citizens. Indonesia has enacted Act Number 14/2008 (FOI Act) and run into force in 2010, which contains 14 obligations to State-Owned Enterprises (SOE’s). This paper will focus to elaborate SOE’s compliance with its basic obligations in this FOI Act, resulted in monitoring and evaluation conducted by Central Information Commission (CIC); the problems; the challenges, and the opportunities. This study uses library research, especially using secondary data from the CIC annual ranking reports. The results show that (i) good corporate governance is actually in line with transparency principle; (ii) there is an increase participation level of SOE’s in complying with the FOI Act; and (iii) most of SOE’s are placed in ‘uninformative’ category. It is important to find solutions to this compliance problems.